Analisis Faktor yang Mempengaruhi Innovation Resistance dan Intention to Use Terhadap Penerapan Pembayaran Non Tunai - Rifa Alfianu Softina; Faris Mushlihul Amin; Noor Wahyudi (Universitas Diponegoro, 2022)
Pertamina implements the MyPertamina cashless payment system to improve the quality of service to consumers in purchasing Pertamina products. Nevertheless, the MyPertamina application lacks users, as no research has discussed the reason for MyPertamina's low adoption rate; thus, it can be an exciting topic to investigate further. The objective of this research was to gain a better understanding of technological resistance by exploring the factors that contribute to resistance behaviour and intentions to adopt technology for MyPertamina services. The conceptual model was based on social influence, innovation resistance theory, and planned behaviour theory. Data was collected by distributing online questionnaires, and up to 350 data sets were processed using the structural equation model - partial least squares method. The results indicated that traditional and image barriers had a significant positive effect on innovation resistance, and social influence and self-efficacy significantly impacted the intention to use. In comparison, innovation resistance had a negative effect on the intention to use.